A capital contribution to the Serbian diaspora studies - Mitrović, Ljubiša (Sociološki pregled, 2021)
The paper presents a review of the studies in relation to the matter of external migrations conducted by Professor Vladimir Grečić and, in particular, his latest book Serbian Creative Intelligence in the Diaspora. The conclusion is that the value of this monograph is not only in its scholarly contribution to the perception of this important matter, but also in its relevance to the rational establishment of a strategy and upgrading of Serbia’s public policy in the area of home country-diaspora relationship.
Keywords: scholarly research of diaspora; strategy and public policy regarding the diaspora; Serbia; Vladimir Grečić